KNOWLEDGE, ATTITUDE AND AWARENESS OF DENTAL UNDERGRADUATE STUDENTS REGARDING HIV/AIDS PATIENTS - Rahman, Reshma; Kumar mp, Santhosh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of the study was to assess the knowledge, awareness and the attitude of dental students towards HIV/AIDS patients and to know whether knowledge has any influence on the attitude and willingness to treat HIV/AIDS patients. Methods: A self administered structured questionnaire consisting of 19 questions on knowledge, attitude and awareness about HIV/AIDS was distributed among 100 students randomly belonging to third year, final year and intern students of saveetha dental college, saveetha university, chennai. The data extracted were tabulated, statistically analyzed using SPSS Version 20.0 and results obtained. Results: The results revealed that many of the respondents demonstrated a good level of knowledge. The total mean knowledge score was 73% (good knowledge).There was a statistically significant difference of knowledge levels among the third year, final year students and the interns. The overall mean attitude score was 62.7% (negative attitude). There was no statistically significant difference of attitude among the three groups. Conclusion: Majority of dental students in our study have good level of knowledge regarding HIV/AIDS. Final year students have the highest level of knowledge and third year students have minimum level of knowledge regarding HIV/AIDS. Irrespective of the year of study, majority of the students showed a negative attitude towards HIV/AIDS patients and only a few among the interns showed a positive approach towards treating HIV patients. Hence these findings imply that there is a need to improve educational methods to more clearly address misconceptions and attitudes towards the disease. Â Â